The edge of the precipice : why read literature in the digital age? - Socken, Paul, 1945- (McGill-Queen's University Press, 2013)
Can a case be made for reading literature in the digital age? Does literature still matter in this era of instant information? Is it even possible to advocate for serious, sustained reading with all manner of social media distracting us, fragmenting our concentration, and demanding short, rapid communication? In The Edge of the Precipice, Paul Socken brings together a thoughtful group of writers, editors, philosophers, librarians, archivists, and literary critics from Canada, the U.S., France, England, South Africa, and Australia to contemplate the state of literature in the twenty-first century. Including essays by outstanding contributors such as Alberto Manguel, Mark Kingwell, Lori Saint-Martin, Sven Birkerts, Katia Grubisic, Drew Nelles, and J. Hillis Miller, this collection presents a range of perspectives about the importance of reading literature today.